Metode Narcotics Religious dalam Rehabilitasi Korban Penyalahgunaan Narkoba (Studi Kasus di Yayasan Grapiks Cileunyi Bandung) - Mukhtar Gojali; Hasan Mud'is; Tamami; Reiha Fadila (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
Rehabilitation is restoration or return to its original state. In this case, people who abuse drugs or people who are already addicted to drugs, if they enter a rehabilitation place, the goal is to return themselves to their original state (before drug use) so that they always carry out their own functions properly. Meanwhile, the religious narcotics method is a method developed by the Grapiks Foundation as an effort to rehabilitate drug abuse victims. This study aims to determine the profile of the Grapiks Foundation, know how the religious narcotics method is in rehabilitating drug abuse victims, and to find out the impact felt by clients who are undergoing rehabilitation at the Grapiks Foundation when going through each stage of the religious narcotics method. Researchers used qualitative methods with a case study approach, researchers conducted observations, interviews and documentation. The sample in the study amounted to 7 respondents, with details of one as an agency representative, 3 rehabilitation staff, and 3 active clients who are undergoing inpatient rehabilitation at the Grapiks Foundation. The results of this research can be concluded that the Grapiks Foundation is a foundation that was legally established in 1999, and focuses on the field of drugs since 2004 until now. The religious narcotics method is applied as an effort to rehabilitate victims of drug abuse at the Grapiks Foundation through 3 stages. First, education, education is the provision of material related to the 7 steps in the religious narcotics method, namely intention, repentance, prayer, effort, tawakal, gratitude and istiqamah, the scope of discussion includes understanding, verses of the Qur'an, benefits, urgency, way to example in everyday life. The goal is that the client is able to understand the important and basic things related to the 7 steps of this method. Second, implementation, which is the implementation of the 7 steps that have been given in accordance with the rehabilitation staff guidelines, for example, the client is assigned a task for each step. Third, evaluation, which is an assessment / follow-up related to the tasks assigned by the rehabilitation staff during the implementation stage. The impact felt by the client after going through each stage of the religious narcotics method is the emergence of awareness to understand religion, increasing religious knowledge, being able to reintroduce Arabic letters and being able to recite the Koran, feeling calm, can solidify the heart, life becomes more purposeful, becomes be grateful for what God has given, pray to Allah when faced with problems, thoughts become clearer, feel there is special satisfaction and feel that they have a guide for life.